Habilidades intelectuais de idosos: um estudo longitudinal - Ana Carolina Zeferino Menezes (2008)
The certification about aging of worlds population has contributed to the increase of researches about the elders. Data has indicated that aging, even if healthy, leads to a normal decrease in cognitive performance. The following study aims to investigate the intellectual development of elder people in different domains assessed by WAIS-III. Results showed negative correlations between age and vulnerable abilities, while correlations between age and stable abilities were positive. Even though not all of the correlations were statistically significant, they happen to occur in the expected directions. Approaching from a longitudinal design and in accordance with the samples features, the 47 participants were divided in two age groups: younger seniors (ranging until 74 years old) and older seniors (over 75 years old). Results displayed that younger seniors presented gains in the abilities assessed, however, they were significant only in two indexes. When it comes to verbal comprehension and language capacities, the gains were expected. On the other hand, memory, perceptual organization, processing speed, performance and total IQ did not exhibit the same fashion most of the studies report. Results for the older seniors were congruent with literature: vulnerable abilities (perceptual organization, memory and processing speed) demonstrated decrease eight years after the first evaluation. However not all results were significant, they go in the same direction of the researches that define significant decreases after 75 years of age. Two independent samples were compared in order to verify signs of generation effects. Exploratory analysis was run and, even though there was only a small interval between the means of the year of birth, it was found tendencies of increase in performances of the participants with ages over 60 years old. The results are in agreement with the ones reported by Flynn (2006). To sum up, these results show that the elderly had not presented decrease in the intellectual abilities assessed until the age of 74 years old, starting from this age, though, some loss were initiated. The only ability that displayed a remarkably higher decrease was processing speed. Data from longitudinal design are not sufficient to describe a trend in the general decrease of the elderly. Some other variables, besides the ones examined in this research, might be related to this standard. Further investigations are needed to examine them and to determine how much does age explain the intellectual tendency of the elders.